Concepções de nação e estado nacional dos docentes de Geografia: Belo Horizonte no final do segundo milênio - Rogata Soares Del Gaudio (2006)
This research aims to understand the conceptions of the Geographic teachers that work in Belo Horizonte at the end of the second rnillenniurn, ahout nations and national states. This is a qualitative research situated in the extension set of the Criticai Theory and into the boundaries between three sciences: Poiitic Science, Geography and Education. We consider the teachers as producers and a subject to knowiedge in and on their daiiy jobs, as weii as it is guiding principies. We consider further the teachers knowiedge as theoreticai (subjects, aiso), practicai, about and originated from practice and that this practice aiiows the permanent (re)buiiding of their knowiedge, influencing their vaiues and identity. Anaiyzing the preferred quaiities in good teachers, especiaiiy for the secondary education, we can accentuate the importance of the teacher being a good person, having discipiinary knowiedge and teaching methodoiogy, besides being abie to give sense to the contents and teach a reasoning way, adding different fields of human knowiedge. lhe choice as weii as in Geography as in the nations and nationai states concepts, reiates to the proper foundation of this discipiine itseif, as it is connected to the state and to a certain way to propagate the nationai ideoiogy. We tried to research if the Geography, in speciai the Geography education, stiii constitutes a way for nationai ideoiogy dissemination. lhe interviewed teacher s conceptions about nations and nationai states are known for a necessity to materiaiize and specify them as the practice with new contents, such as new worid order, conflicts and tension points bring them into context. lhis way, interviewed teachers differs nations and nationai state, especiaily, based in some eiements iike cuiturai question, ethnic, identity and the feeiing (to beiong to) for the nations; and for the nationai states the sovereign possession over the territory, the existence of the state machine, and the recognition of their sovereignty by other nationai states. lhere is aiso, from the some interviewed teachers part, the resource of the intensive use of the term country, sometimes appointing to one, sometimes to the other. Aiso we have to consider that, in order to construct the nationai ideoiogy in Brazii, the Geographic speech resource was more intense than the Historicai speech, since the construction of our identity is based in eiements iike the territoriai extension, nature (both aspects heaveniy and infemai) and the presence of a pacific and orderiy peopie.